Significance of Medical Examination of Seafarers: A Descriptive Study About Maritime Industry - Tiwari, Jaya (Digital Repository of Theses - SSBM Geneva, 2025)
Significance of Medical Examination of Seafarers: A Descriptive Study About the Maritime Industry The maritime industry plays a crucial role in global trade by enabling the movement of goods and services across international waters. At the heart of this industry are seafarers, who operate vessels under challenging conditions that demand optimal health and fitness. Given the nature of their work—long voyages, physically demanding tasks, and limited access to medical care—ensuring their medical readiness before embarking on a voyage is crucial. This study explores the awareness and satisfaction levels of Indian seafarers regarding Pre-Employment Medical Examination (PEME), highlighting its significance in promoting maritime health and operational efficiency. Study Focus and Objectives This research aims to: • Analyze Regulatory Frameworks: Discuss national and international medical standards governing seafarers, including compliance with the International Labour Organization (ILO), International Maritime Organization (IMO), and Maritime Labour Convention (MLC) 2006 regulations. • Evaluate Awareness: Assess Indian seafarers’ knowledge and understanding of PEME procedures, including their scope, importance, and regulatory requirements. • Measure Satisfaction Levels: Examine how satisfied seafarers are with PEME protocols and whether they feel the medical examinations adequately assess their fitness for duty Identify Common Health Issues: Highlight prevalent medical conditions among Indian seafarers and their potential impact on occupational performance and maritime safety. • Benefits of PEME (pre-employment medical examination) to the Maritime Industry. Key Findings • Regulatory Compliance Gaps: Although India follows MLC 2006, STCW Code, and Merchant Shipping Rules, certain disparities exist in the standardization of medical screening practices, which may affect the trust and effectiveness of PEME. • High Awareness with Minor Gaps: Most Indian seafarers are well-informed about PEME procedures, with strong understanding across core medical tests. Some uncertainty exists around less frequently encountered screenings. • Satisfaction Levels Are High: Most Indian seafarers regard PEME as purposeful and beneficial, particularly in early disease detection and overall health assessment. Few expressed neutral views, highlighting scope for further refinement. • Prevalent Health Conditions: Common health concerns among Indian seafarers include hypertension, diabetes, obesity, hearing loss, musculoskeletal disorders, and mental health challenges—reinforcing the necessity of comprehensive PEME protocols. • Enhanced crew health, risk reduction, and cost savings are direct benefits of pre- employment medical examinations. Recommendations for the Maritime Industry 1. Strengthen Awareness Campaigns – Employers and regulatory bodies must educate seafarers on the scope and necessity of PEME through workshops, online training, and onboard briefings. 2. Enhance Standardization & Transparency – Ensuring uniform medical screening protocols across different clinics will reduce inconsistencies and improve trust among seafarers. 3. Expand Psychological Health Evaluations – Mental health screening should be integrated into PEME protocols, as maritime workers face high stress levels and isolation that can affect performance. 4. Leverage Telemedicine for Remote Health Support – Using telehealth solutions can help seafarers receive preliminary medical guidance before undergoing full examinations, thereby reducing procedural delays. 5. Regulatory Improvements & Industry Collaboration – Policymakers must review PEME frameworks regularly, ensuring medical assessments align with evolving health risks and industry demands. Conclusion Medical examinations are a critical component of seafarer health management, ensuring fitness for duty and minimizing operational risks in the maritime industry. Given India's significant role in global seafaring, further development of Pre-Employment Medical Examination (PEME) protocols to enhance awareness, satisfaction, and standardization would greatly benefit both individual seafarers and the wider industry. By addressing knowledge gaps and enhancing medical evaluation practices, stakeholders can build a health-focused maritime work environment, ensuring safer seas and more resilient workforce operations. KEYWORDS: Pre-Employment Medical Examinations (PEME), Seafarers, ILO (International Labour Organization), IMO (International Maritime Organization), MLC Maritime Labour Convention (2006).